2007
DOI: 10.1097/01.prs.0000263729.26936.31
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Bilateral Lower Abdominal Free Flaps for Unilateral Breast Reconstruction

Abstract: This study suggests that bilateral, bipedicled, abdominal free flaps for unilateral breast reconstruction can be used safely with a high degree of success. These combined flaps provide for enhanced vascular perfusion of the lower abdominal flap territory, allowing for harvest of larger volumes of tissue for reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 117 publications
1
30
0
Order By: Relevance
“…41 Most authors considered skin loss between 10 and 20 percent 17,18,20,42-45 as their cutoff for inclusion, although some authors labeled flaps with less than 5 percent skin loss as "partial necrosis," 46,47 and others categorized skin loss greater than 20 percent as "partial necrosis." 19,35,39,48 Fat necrosis had a range of definitions, including (1) absolute size (lumps >0.5 cm, 49 >1 cm, 6,25,39,50 >2 cm, 15,40,51 >3 cm 16 confirmed not to be malignant recurrence) detected clinically or by ultrasound 49,52,53 and/or mammography 46,54 , (2) proportion of volume of flap 18,43 , and (3) incidence of secondary operations to address fat necrosis.. 21,22,[55][56][57] Other authors chose to describe necrosis as "minor," 58 "minimal," 59 or "limited." 60 Another variable in fat necrosis reporting was the time frame-many authors reported detection rates at 2 39 to 3 6,15 months after the initial reconstruction, but others reported rates at 1 month 41 or even 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…41 Most authors considered skin loss between 10 and 20 percent 17,18,20,42-45 as their cutoff for inclusion, although some authors labeled flaps with less than 5 percent skin loss as "partial necrosis," 46,47 and others categorized skin loss greater than 20 percent as "partial necrosis." 19,35,39,48 Fat necrosis had a range of definitions, including (1) absolute size (lumps >0.5 cm, 49 >1 cm, 6,25,39,50 >2 cm, 15,40,51 >3 cm 16 confirmed not to be malignant recurrence) detected clinically or by ultrasound 49,52,53 and/or mammography 46,54 , (2) proportion of volume of flap 18,43 , and (3) incidence of secondary operations to address fat necrosis.. 21,22,[55][56][57] Other authors chose to describe necrosis as "minor," 58 "minimal," 59 or "limited." 60 Another variable in fat necrosis reporting was the time frame-many authors reported detection rates at 2 39 to 3 6,15 months after the initial reconstruction, but others reported rates at 1 month 41 or even 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…10 Other authors have reported the use of two hemiflaps to the same breast, each side with its own vascular pedicle. 9 However, these techniques require a large number of microvascular anastomoses and possibly additional recipient vessels. In our experience, the use of vascular delay provided us with the extra flap volume needed, abrogating the need of bipedicled tissue transfer.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from the American Society of Plastic Surgeons, 8 more than 6,000 DIEP-flap breast reconstructions were performed in 2008. When the entire infraumbilical abdominal adipose tissue flap is needed for the breast reconstruction, two separate hemiabdominal DIEP flaps can be elevated 9 or a bipedicled flap can be raised. 10,11 Although the use of vascular delay in breast reconstruction almost paralleled the development of the TRAM flap and may have followed it into the era of free-tissue transfer, to our knowledge, no author has described the use of the delay phenomenon with DIEP flaps.…”
mentioning
confidence: 99%
“…5 Although the use of bilateral pedicles for unilateral breast reconstruction is not technically different, it is important to emphasise that the morbidity at the donor site and magnitude of operative complexity may be greater. 1 The advantages of using the SIE vessels during doublepedicled abdominal free flap reconstruction include a reduced flap harvest time (as the SIEA is easier to raise than a DIEP flap); large calibre venous drainage, establishment of venous drainage of the flap through both the superficial and deep systems; simpler second set anastomoses at the recipient site on the chest wall, and lower donor site morbidity due to spared muscle and fascial dissection on one side.…”
Section: Dear Sirmentioning
confidence: 99%
“…The use of a double pedicle flap design for unilateral breast reconstruction may overcome some of these factors, maximising the use of all the lower abdominal tissue, by recruiting an additional vascular territory, particularly when harvesting a large volume of tissue to match the contralateral breast. 1 These flaps comprise 20% of all microsurgical breast reconstructions in the senior author's current practice. The two halves of the bipedicled free abdominal flap can be vascularised via intra-flap or extra-flap anastomoses.…”
Section: Dear Sirmentioning
confidence: 99%